The study of psychometric test for detection and assessment in subclinical hepatic encephalopathy - Kanwar, Gopal; Singh, Sanjay; Pandey, Sachin; Paikra, Shashi (International Journal of Medical Research and Review, 2018)
Background: During past two decades, psychometric tests have been used extensively for detection of SHE. However, the results have been variables with different tests. In real practice we require the tests, which can be administered quickly by treating physician with simplicity and with simple instrument or only with a simple form. Objective: (1) To apply a battery of psychometric tests in cases of cirrhosis of liver. (2) To correlate findings of psychometric tests with Child`s index of severity for cirrhosis of liver. Methodology: 25 patients of cirrhosis of liver diagnosed by ultrasonography, biochemical and clinical evidence, admitted in the Medicine ward, will constitute the study group. These patients will undergo a battery of psychometric tests and EEG along with other routine hematological and radiological test. 25 control group with confounding factors as age, sex, education and socioeconomic status. Results: We observed that on WAPIS test cirrhotic performed significantly worse than controls. Mean IQSD non-Alcoholic cirrhotic on WAPIS was [67.7811.29] and Mean IQSD of alcoholic cirrhotics was (66.459.71). On analysis of data the difference was not significant (p>0.005). Taken together the performance test was abnormal in 14 (56%) cases. Conclusion: We concluded that for quick assessment of mental status and screening for detecting SHE in cases of cirrhosis of liver with portal hypertension, TMT test is useful and for complete assessment of cerebral function derangement WAPIS is most sensitive and complete test.